2019
DOI: 10.5586/aa.1757
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of adverse effects of salt stress on germination, growth, photosynthetic efficiency and yield in maize (Zea mays L.) through magnetopriming

Abstract: The efficiency of magnetopriming was evaluated for mitigation of the detrimental effects of salt stress on maize germination, growth, photosynthesis, and yield of maize plants. Maize seeds were pretreated with 200 mT of static magnetic field (SMF) for 1 h to assess the impact of SMF on the germination, seedling vigor, growth of plant, photosynthetic performance, ROS content, and yield under salt stress. The seedling characteristics of maize were negatively influenced by salt stress. However, SMF-pretreated mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 38 publications
5
48
0
Order By: Relevance
“…In contrast, SMF‐priming significantly increased the early growth characteristics of the seedlings along with an increase in enzyme activities (α‐amylase, protease and NR), ROS and NO content in the absence and presence of salt stress. This effect of magnetic biostimulation of seed germination using SMF has been reported in several plant species in non‐stress and abiotic stress conditions (Kataria et al , Baghel et al , Kataria et al , ). SMF pre‐treatment increase the germination and vigor of seedlings by affecting the biochemical processes like free radical formation and by raising the enzymes activity related to seed germination (Kataria et al , Anand et al , Baghel et al ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In contrast, SMF‐priming significantly increased the early growth characteristics of the seedlings along with an increase in enzyme activities (α‐amylase, protease and NR), ROS and NO content in the absence and presence of salt stress. This effect of magnetic biostimulation of seed germination using SMF has been reported in several plant species in non‐stress and abiotic stress conditions (Kataria et al , Baghel et al , Kataria et al , ). SMF pre‐treatment increase the germination and vigor of seedlings by affecting the biochemical processes like free radical formation and by raising the enzymes activity related to seed germination (Kataria et al , Anand et al , Baghel et al ).…”
Section: Discussionsupporting
confidence: 64%
“…After 5 d (120 h of seed imbibition), the number of germinated seeds compared to total number of the seeds was counted to assess the percentage of germination. The stress tolerance index for germination was calculated as suggested by Baghel et al () for non‐primed and SMF‐primed seeds: stress tolerance index of germination (GSTI) = (PI of seeds in salt stress / PI of seeds of controls) × 100, where PI is the promptness index calculates as follows PI = nd 1 (1.00) + nd 2 (0.75) + nd 3 (0.50) + nd 4 (0.25), nd is the number of seeds germinated on the day of observation. And nd 1 , nd 2 , nd 3 and nd 4 are then number of seeds germinated, respectively, on the first, second, third and fourth day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed, in seedlings derived from treated seeds, an increase in stem length, stem diameter, leaf area, and fresh and dry weight, even under saline conditions. Several studies have shown that SMF can increase the seed germination and seedling vigor under salt and heavy metal stress in chickpea, soybean, barley, mung bean, and maize [ 20 , 21 , 47 , 84 , 85 ].…”
Section: The Effects Of Mf Application On Plant Developmentmentioning
confidence: 99%
“…Salinity is another very important yield limiting factor in crop lands, principally in arid and semiarid regions of the world (Baghel et al, 2019). Salinity stress not only influences vegetative growth, but also affects reproductive structures and translocation of C and N to developing seeds and fruits.…”
Section: Introductionmentioning
confidence: 99%